Historical data provides context for recent monitoring and demonstrates 100 years of declining estuarine health - Hannah F. E. Jones; Stephen Hunt; Janine Kamke; Michael Townsend (New Zealand Journal of Marine and Freshwater Research, 2022)
Estuaries are complicated systems to manage effectively, requiring the monitoring of robust environmental indicators to assess health and detect changes. Routine estuarine monitoring programmes in New Zealand have only existed for 30 years at most, but estuaries have been significantly affected by anthropogenic pressures for at least 100 years. We reconstructed long term changes in indicators of estuarine health using historical information from sediment cores and aerial photographs, and combined this information with recent monitoring data. This study is focused on four estuaries in the Waikato region of New Zealand, but the findings are likely applicable elsewhere. Sediment accumulation rates increased by orders of magnitude c. 100 years ago, but mangrove forests only started to rapidly expand c. 50 years ago, which coincided with the intensification of agriculture and urban development, and resultant declines in freshwater quality. Over the past 20 years, state of the environment monitoring shows declines in benthic health at most monitoring sites, as well as continuing sediment accumulation and mangrove expansion in some places. This adds to the weight of evidence that environmental management has not been sufficient to safeguard estuarine health and demonstrates the magnitude of change in these systems over the past 100 years.